Wound Healing Process as the Most Appropriate Modality of Cancer Therapy - Liau, Ming C.; Craig, Christine L.; Baker, Linda L. (European Journal of Applied Sciences, 2023)
President Biden of USA declared cancer moonshot initiative on Sept. 12, 2022 to urge the health profession to come up solutions to save 50% of cancer patients in the following 25 years. Cancer therapies were dominated by strategy based on killing of cancer cells in the past, which have been drilled through as a presidential project, but failed to achieve the goal to win the war on cancer. Obviously, a drastic change of strategy is necessary to fulfill moonshot of President Biden. Wound healing requires the proliferation and the terminal differentiation of progenitor stem cells (PSCs). Wound healing comes naturally, because the nature creates chemo-surveillance to ensure perfection of wound healing. Healthy people are able to maintain a steady level of wound heading metabolites active as differentiation inducers (DIs) and differentiation helper inducers (DHIs) to promote terminal differentiation of PSCs through destabilization of abnormal methylation enzymes (MEs). The functionality of chemo-surveillance can be damaged under pathological conditions triggering the production of tumor necrotic factor (TNF) to cause cachexia symptoms. A manifestation of cachexia symptoms is the excessive urinary excretion of wound healing metabolites to affect terminal differentiation of PSCs to heal wound, allowing PSCs to evolve into cancer stem cells (CSCs), and then to progress to faster growing cancer cells (CCs) through activation of oncogenes and/or inactivation of suppressor genes. Since cancer is caused by wound unhealing. Thus, wound healing process offers the most appropriate modality of cancer therapy. CDA-2 is a preparation of wound healing metabolites purified from urine, which has superb therapeutic efficacy against myelodysplastic syndrome (MDS). MDS is a disease caused by the build up of CSCs unable to undergo terminal differentiation. Apparently, wound healing metabolites are the best medicine to eradicate CSCs. For the therapy of cancer, we propose to add another set of DI + DHI consisting of synthetic products to target CCs, since CCs are known to express high levels of salvage enzymes to support their faster growth. CDA formulations definitely can fulfill cancer moonshot. Perpetual replication of CCs is the most outstanding feature of cancer. Naturally, killing of CCs becomes the choice of cancer establishments to combat cancer in the past. This modality of cancer therapy has been drilled through as a presidential project, but failed to achieve the goal to win the war on cancer. The contribution to damage chemo-surveillance and the inability to eradicate CSCs are responsible for the failure to save cancer patients. A combination therapy with CDA formulations can eliminate such deficit to fulfill cancer moonshot.